PEMANFAATAN DAUN KANGKUNG MENJADI KERUPUK KANGKUNG DALAM UPAYA PEMBERDAYAAN MASYARAKAT DI DESA ILOMANGGA, KECAMATAN TABONGO, KABUPATEN GORONTALO - Sandalayuk, Marselia; Ernikawati, Ernikawati; Sandalayuk, Daud; Pakai, Algifar; Napu, Wahyu H.; Yunus, Reinaldi; Irni, Julaili; Junaidi, Koko (Universitas Gorontalo, 2025)
Water spinach is a plant that is a type of vegetable and is grown as food. Water spinach is widely sold in markets. Based on observations made, it shows that the local potential in llomangga Village is Sayur Kangkung. Most commonly found are kale vegetable farmers and kale vegetables have become the daily food of the llomangga community. Water spinach has become a consumer ingredient but its utilization is still lacking. For this reason, as a means of utilizing water spinach, Community Service College students process water spinach leaves into a material that is useful and has economic value. Like Kangkung Crackers. Keywords : Water spinach leaves, Community empowerment, Ilomangga